Onomastic interferences in the language of migration - Jieanu, Ioana (Vestnik za tuje jezike, 2015)
In case of bilingual speakers, proper names undergo different transformations, depending on the contextual character of a manifestation of meanings, "the relationship between the proper name and the denoted object being temporary, dependent on the verbal and situational context" (Tomescu 1998: 1). Within the scope of the current economic migration of Romanians to Spain and Italy, the names of Romanian people have undergone various modifications under the influence of Spanish and Italian onomastics. In the present work, the performance of two main tasks is described: an analysis of the interferences which emerge within communication, in case of the proper names of Romanian people who have emigrated to Spain and Italy; and classification of the proper names of new-born children within Romanian families that have settled in these countries.
Keywords: human migration; migracije; jeziki v stiku; jezikovna interferenca; onomastics; onomastika; romunščina; Italian; italijanščina; Spanish; španščina; Italy; Italija; Spain; Španija